جەنگی دەروونی و ئامرازەکانی گەیاندن و بەرەنگاربوونەوەی - حسن, ئاشتی حەمەصالح حسین (Sulaimani Journal for Humanities, 2023)
The importance of psychological warfare started with the beginning of human life in order to reach their goals by changing the direction and behavior of others, and in the end it had a major role in reaching the goals and resolving battles in favor of the strongest, and this long history of using psychological warfare made thousands of heroes, until their lives, experiences and their sayings have become history and memory either in a positive or negative light. It may be repeated and glorified by some, and subjected to reproach and criticism by others. Undoubtedly, psychological warfare has a strong relationship with many sciences, including psychological sciences, social sciences, media and communication sciences, etc. The fact that psychological warfare is called the Cold War directs the mind and emotion of the enemy. Therefore, the parties of psychological warfare at all times needed some means of communication to reach their goals. It is worth noting that the goals of psychological warfare have not changed significantly over time, but the methods and means used have changed with technological development, so that it was a catalyst for achieving the goals of psychological warfare in an easier, faster and cheaper way. One of the aims of this research was to find out what psychological warfare is and how to utilize the means of communication in psychological warfare and how to confront psychological warfare that is done through the media. In the end, the researcher reached a set of results, including: 1. In order to reach their goals, psychological warfare parties at all times used contemporary means of communication, and technological development had a prominent role in reaching the goals of psychological warfare in a faster and easier way. 2. After World War II, the terms cold war, “soft power” and “smart power” were added to the political dictionary, and then the countries continued by using advanced media technology.
Keywords: Key words (psychological warfare; means of communication; use; confrontation)